Method Development and Validation in Food and Pharmaceutical Analysis - Yoon, In-Soo; Cho, Hyun-Jong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers a wide range of topics including, but not limited to, new analytical and bioanalytical methods relevant to the separation, identification, and determination of substances in pharmaceutics, pharmacokinetics, nanobiotechnology, clinical chemistry, and related disciplines; methods for the identification of bioactive compounds in functional foods and medicinal plants; applications of chromatography and allied techniques in biomedical sciences.